Kinematic Changes in the Uninjured Limb After a Traumatic Brachial Plexus Injury - Souza, Lidiane; Lustosa, Luiggi; Silva, Ana Elisa Lemos; Martins, José Vicente; Pozzo, Thierry; Vargas, Claudia D. (Frontiers in Human Neuroscience, 2021)
Background: Traumatic brachial plexus injury (TBPI) typically causes sensory, motor and autonomic deficits of the affected upper limb. Recent studies have suggested that TBPI can also affect the uninjured limb. Objective: Our objective was to investigate the kinematic features of the uninjured upper limb in participants with TBPI. Methods: Eleven participants with unilateral TBPI and twelve healthy controls matched in gender, age and anthropometric characteristics were recruited. Kinematic parameters collected from the index finger marker were measured while participants performed a free-endpoint whole-body reaching task and a cup-to-mouth task with the uninjured upper limb in a standing position. Results: For the whole-body reaching task, lower time to peak velocity (p = 0.01), lower peak of velocity (p = 0.003), greater movement duration (p = 0.04) and shorter trajectory length (p = 0.01) were observed in the TBPI group compared to the control group. For the cup-to-mouth task, a lower time to peak velocity was found for the TBPI group compared to the control group (p = 0.02). Interestingly, no differences between groups were observed for the finger endpoint height parameter in either of the tasks. Taken together, these results suggest that TBPI leads to a higher cost for motor planning when it comes to movements of the uninjured limb as compared to healthy participants. This cost is even higher in a task with a greater postural balance challenge. Conclusion: This study expands the current knowledge on bilateral sensorimotor alterations after unilateral TBPI and should guide rehabilitation after a peripheral injury.